Investigations on the microstructure and mechanical properties of laser welded dissimilar galvanized steel-aluminum joints - Yüce, Celalettin; Karpat, Fatih; Yavuz, Nurettin (Springer London Ltd, 2019)
In this study, galvanized high-strength steel and aluminum alloy sheets were laser-welded in zero-gap lap joint configuration. In order to determine the influences of the heat input levels, microstructural and mechanical properties of the joints were investigated. The weld bead geometry, microstructure, and intermetallic phases at the interface of welded joints were investigated using an optical microscope and scanning electron microscopy (SEM) with energy-dispersive spectroscopy (EDS) at different heat input levels. Mechanical properties and microhardness distribution of the welded joints were examined according to the weld bead dimension. The results revealed that there is a correlation between the weld seam geometry and intermetallic phase formation. At relatively high heat input level, the penetration depth increased, and thick Al-rich intermetallic layer was observed at the interface of the weld seam, which deteriorated the tensile strength of the joint. It has been found that without the need for any additional precaution, the thickness of the IMC layer can be limited to 5-15 mu m when the optimum welding parameters were conducted. The experimental results showed that with limited heat input and penetration depths, up to 108.7-N/mm tensile strength could be achieved and fracture initiated at the weld seam-steel interface.
Keywords: Laser welding; Steel-aluminum; Intermetallic layer; Mechanical properties